The Mediating Role of Professionalism in the Relationship Between Organizational Culture, Transformational Leadership, and Asatidz Performance - Muhammad Salim Faroghy; Bibin Rubini; Iyan Irdiyansyah (Indonesian Journal of Business Analytics, 2026)
This study examined the effects of Pesantren Organizational Culture and Transformational Leadership on Asatidz Performance, with Professionalism as a mediating variable. The study employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 150 asatidz selected through proportionate stratified random sampling from several pesantren institutions. The analysis applied the Higher-Order Construct approach with the disjoint two-stage method using SmartPLS 4. The results showed that Professionalism had the strongest positive effect on Asatidz Performance. Pesantren Organizational Culture significantly influenced both Professionalism and Asatidz Performance. Transformational Leadership significantly affected Professionalism but did not directly influence Asatidz Performance. Mediation analysis revealed that Professionalism partially mediated the relationship between Pesantren Organizational Culture and Asatidz Performance, while fully mediating the relationship between Transformational Leadership and Asatidz Performance. These findings indicate that professionalism is the primary mechanism through which organizational culture and leadership contribute to improving the performance of asatidz. The study highlights the importance of strengthening professional values, organizational culture, and leadership practices to support sustainable performance improvement in pesantren educational institutions.